![\large \boxed{y=a_0\left( 1-(1)/(6)x^2+(1)/(168)x^4-(1)/(11088)x^6+...\right)}](https://img.qammunity.org/2021/formulas/mathematics/college/78j7pbmm8zjgragnuuxjiigqad27kkpj4c.png)
Hello, please consider the following.
The equation is
![2x^2y](https://img.qammunity.org/2021/formulas/mathematics/college/t6iqhd73owmawjgorvbagf7nqkctioiumm.png)
Assume that, on a given domain where the sum is defined,
![\displaystyle y=\sum_(n=0)^(\infty) a_nx^n](https://img.qammunity.org/2021/formulas/mathematics/college/8g3dgd7432pipi6vzb5avce9tz38c642up.png)
is a solution of the equation and we will find a recursion formula for the
, then
![\displaystyle y=\sum_(n=0)^(\infty) a_nx^n\\\\y'=\sum_(n=1)^(\infty) na_nx^(n-1)\\\\y''=\sum_(n=2)^(\infty) n(n-1)a_nx^(n-2)](https://img.qammunity.org/2021/formulas/mathematics/college/lf8sjfkxnakvk8gro19n0d6qq28we1xfpp.png)
So the equation becomes
![\displaystyle 2x^2y'+xy'+x^2y=\sum_(n=2)^(\infty) 2n(n-1)a_nx^2x^(n-2)+\sum_(n=1)^(\infty) na_nxx^(n-1)+\sum_(n=0)^(\infty) a_nx^2x^n\\\\=\sum_(n=2)^(\infty) 2n(n-1)a_nx^(n)+\sum_(n=1)^(\infty) na_nx^n+\sum_(n=0)^(\infty) a_nx^(n+2)\\\\=\sum_(n=2)^(\infty) 2n(n-1)a_nx^(n)+\sum_(n=1)^(\infty) na_nx^n+\sum_(n=2)^(\infty) a_(n-2)x^(n)\\\\=a_1x+\sum_(n=2)^(\infty) 2n(n-1)a_nx^(n)+ na_nx^n+a_(n-2)x^(n)\\\\=a_1x+\sum_(n=2)^(\infty) \left((2n-2+1)na_n+a_(n-2)\right)x^(n)](https://img.qammunity.org/2021/formulas/mathematics/college/2uu6ig2up663jye92857wvzbb04hqkyuhp.png)
And this is equal to 0, so we can say that
![a_1=0\\(2n-1)na_n+a_(n-2)=0 \ \ \text{for n }\geq 2](https://img.qammunity.org/2021/formulas/mathematics/college/7igdas0f5sf5uxx976ixry4bi7czc00pwl.png)
It comes
![\boxed{a_n=-(a_(n-2))/(n(2n-1))}](https://img.qammunity.org/2021/formulas/mathematics/college/m6x5xyk115ekzsj0x3qrgs0c5w7yd4dw86.png)
![a_1=0 \ so \ a_3=0 \ \ and \ \ a_5=0 \ \ so \ \ a_(2n+1)=0\\a_2=(-a_0)/(2(4-1))=(-a_0)/(2*3)=-(a_0)/(6)\\\\a_4=-(a_2)/(4(8-1))=(a_0)/(2*3*4*7)=(a_0)/(168)\\\\a_6=-(a_4)/(6(12-1))=-(a_0)/(2*3*4*7*6*11)=(-a_0)/(11088)](https://img.qammunity.org/2021/formulas/mathematics/college/ax0g29n6t9lxfy48goyxg8yx5k1059beki.png)
So
![y=a_0\left( 1-(1)/(6)x^2+(1)/(168)x^4-(1)/(11088)x^6+...\right)](https://img.qammunity.org/2021/formulas/mathematics/college/d9ts6m7o0q42u28sujwu5u7fkiqv3pr982.png)
We can go further to find a generic expression but only 3 non-zero terms were requested.
Hope this helps.
Do not hesitate if you need further explanation.
Thank you